A basic guide for sampling and preparation of extant and fossil bones for histological studies - Cerda, Ignacio Alejandro (2020)
The study of bone microstructure of fossil vertebrates (i.e. paleohistology) has demonstrated to be a very important source of paleobiological information. Paleohistological studies are based on the standardized analysis of petrographic thin sections. Although the development of new technologies (e.g. microtomography) have provided non-destructive procedures for the study the fossil tissues, thin sections are still the main information source in paleohistology. In this contribution, we provide a detailed protocol for sampling and thin sectioning preparation of bone tissue from both fossil and extant vertebrates. We describe the most common procedures for sample obtainment and also some particular differences, which are related to variations in the equipment and sampling techniques. The main objective of this contribution is to offer an alternative protocol for laboratories in formation and/or with limited funding.